Pre-trial investigation as a major form of investigation: the question of reforming at the present stage - Пильгун, Н. В.; Бородін, Є. В.; Присяжнюк, І. О. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
Discovered the essence of pre-trial investigation as a form of pre-trial investigation, analyzes the features of the new Criminal Procedure Code of Ukraine, noted its positive and negative sides.